1956
DOI: 10.1103/physrev.101.778
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Ratio Method Applied to the Measurement ofL-Meson Masses and the Energy Balance in Pion Decay

Abstract: was evinced. It was concluded that the half-life obtained was due to pileup of pulses with lower energy; such pileup should display a half-life of one-half the 7.7-min half-life.The lack of an observed internal conversion line indicates that the 0+, T=l level 2 probably lies above the 7=3, T-0 level. This would require a positron end point for the 0.95-sec activity in K 38 of energy > 4.84 Mev. In any case the above argument indicates that the energy of the transition is greater than 4.76 Mev. CONCLUSIONSThe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

1957
1957
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…Powers of the dimension bearing electric charge must appear in either a quantum-mechanical parameter η or in the classical plasma coupling parameter g, with g 2 bringing in a factor of the plasma density. Long ago, Barkas et al [17] 5 Whenη pb is small, the function G has a term of order lnη pb that adds to the ln g pb , giving ln(g pb /η pb ) = ln(β κ bvpb ) which converts the classical short-distance cutoff into a quantum cutoff. This is in keeping with the remark above that quantum effects may become important whenη pb becomes small.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Powers of the dimension bearing electric charge must appear in either a quantum-mechanical parameter η or in the classical plasma coupling parameter g, with g 2 bringing in a factor of the plasma density. Long ago, Barkas et al [17] 5 Whenη pb is small, the function G has a term of order lnη pb that adds to the ln g pb , giving ln(g pb /η pb ) = ln(β κ bvpb ) which converts the classical short-distance cutoff into a quantum cutoff. This is in keeping with the remark above that quantum effects may become important whenη pb becomes small.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, the quantum parameters defined in (3.1), 17) are large. In the energy loss problem, these are the only independent dimensionless parameters that entail the quantum unit, Planck's constant .…”
Section: B Quantum Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of different penetration ranges for positive and negative pions in matter made by Barkas and co-workers [1] was the first evidence of deviations of the stopping power of energetic particles from the quadratic dependence on projectile charge Z 1 predicted by the Bethe theory [2]. The origin of this difference, as proposed by Barkas, is due to higher-order terms in the perturbative Born series.…”
Section: Introductionmentioning
confidence: 86%
“…The ARB model [3] was based on the classical harmonic-oscillator model. The treatment was similar to the Bohr model [7] but the analysis was extended to secondorder ͑Z 1 3 ͒ terms, corresponding to the polarization of the atomic oscillators, in the approximation of distant collisions. They showed that the Barkas effect is characterized by the classical parameter gZ 1 0 / v 3 , where Z 1 is the bare-ion charge, 0 the oscillator frequency, v the particle velocity, and g a numerical constant.…”
Section: Introductionmentioning
confidence: 99%